2020
DOI: 10.32890/jgd2020.16.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Between the Rock and a Hard Place: The Africa Union and Democracy Promotion in Africa

Abstract: While the Cold War lasted, the Organization of African Unity (OAU) never considered democracy promotion in member states as a priority. What mattered to the body was the safeguard of the sovereignties of member states. The globalization of the third democratic wave however, changed that as democracy promotion, courtesy of Donor’s aid agenda became a core objective of the OAU/AU. Deploying descriptive, historical, and analytical methods of inquiry with a focus on the African Charter on Democracy, Elections, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Powell, Lasley, and Schiel (2016) found that the African Union (AU)'s anti-coup norms with advocacy of democracy and leverage including trade relations, humanitarian assistance, and democratic neighbours contributed to effectively keeping coup attempts in check. Adding to this, recent literature on the effectiveness of the AU and its responses to coup attempts has been underway to examine how the AU with its democratic norm contributes to a reduction in the occurrence of coups (Basiru and Osunkoya 2020;Cowell 2011;Nte 2020;Souaré 2014;Wobig 2014).…”
Section: Military Coupmentioning
confidence: 99%
“…Powell, Lasley, and Schiel (2016) found that the African Union (AU)'s anti-coup norms with advocacy of democracy and leverage including trade relations, humanitarian assistance, and democratic neighbours contributed to effectively keeping coup attempts in check. Adding to this, recent literature on the effectiveness of the AU and its responses to coup attempts has been underway to examine how the AU with its democratic norm contributes to a reduction in the occurrence of coups (Basiru and Osunkoya 2020;Cowell 2011;Nte 2020;Souaré 2014;Wobig 2014).…”
Section: Military Coupmentioning
confidence: 99%